Infiltrative growth pattern of prostate cancer is associated with lower uptake on PSMA PET and reduced diffusion restriction on mpMRI - Laudicella, Riccardo; Rüschoff, Jan H.; Ferraro, Daniela A.; Brada, Muriel D.; Hausmann, Daniel; Mebert, Iliana; Maurer, Alexander; Hermanns, Thomas; Eberli, Daniel; Rupp, Niels J.; Burger, Irene A. (European journal of nuclear medicine and molecular imaging, 2022)
Recently, a significant association was shown between novel growth patterns on histopathology of prostate cancer (PCa) and prostate-specific membrane antigen (PSMA) uptake on [68Ga]PSMA-PET. It is the aim of this study to evaluate the association between these growth patterns and ADC (mm2/1000 s) values in comparison to [68Ga]PSMA uptake on PET/MRI.